2014
DOI: 10.1016/j.fob.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A novel peptide interferes with Mycobacterium tuberculosis virulence and survival

Abstract: HighlightsThe novel peptide SL3 is a strong binder of the virulence-determining protein ESAT-6.SL3 caused debilitating effects on mycobacterial growth and morphology.SL3 led to accelerated clearance of M.tb and lowered immune response in a pre-clinical mouse model.Microarray analysis of the mutant strain demonstrated a wide-scale transcriptional disruption caused by SL3 in M.tb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Indeed, fewer studies have been reported using human MΦs compared to mouse MΦs. Human MΦs secrete NO at lower levels, show marked functional and phenotypic heterogeneity among tissues, and likely differ in their antimicrobial mechanisms [7][8][9] . This difference is reflected by the nearuniform susceptibility of most mouse strains to low-dose aerosol infection with Mtb versus the differential susceptibility of humans to active disease.…”
mentioning
confidence: 99%
“…Indeed, fewer studies have been reported using human MΦs compared to mouse MΦs. Human MΦs secrete NO at lower levels, show marked functional and phenotypic heterogeneity among tissues, and likely differ in their antimicrobial mechanisms [7][8][9] . This difference is reflected by the nearuniform susceptibility of most mouse strains to low-dose aerosol infection with Mtb versus the differential susceptibility of humans to active disease.…”
mentioning
confidence: 99%
“…Most of the peptides like Human neutrophil defensins (HNPs), Protegrin-1 (PG-1) ( 28 ), Polydim ( 29 ), Pin 2 ( 30 ), Bacteriocins ( 31 ) etc. act on Mycobacterium by disrupting its cell envelope either by forming pore or increases permeabilization by causing membrane depolarization ( 32 ) or by disrupting cell wall biosynthetic pathway ( 33 , 34 ). Beside this several anti-TB peptide perform its inhibition activity by targeting specific enzyme like Mycosin protease-1 (MycP1) ( 35 ), ClpC1 ATPase ( 36 , 37 ), ClpP1P2 peptidase ( 38 ), etc.…”
Section: Resultsmentioning
confidence: 99%
“…ESAT-6 possesses membrane lytic activity due to its helix-turn-helix structure and hydrophobic nature, an attribute that helps M.tb escape phagolysosome, cell-to-cell spread and dissemination. ESAT-6 can alter host defense by decreasing MHC-II expression on macrophages, granuloma formation and decreasing ROS production to aid in intramacrophagial M.tb survival [6]. ESAT-6 or CFP-10/ESAT-6 complex is also known to attenuate host innate immune response by inhibiting production of IL-12, TNF-α, and apoptosis inhibition in M.tb infected macrophages to achieve greater vial load and cell-cell spread [7,8].…”
mentioning
confidence: 99%